Supporting research for sustainable development - Borowiecki, Martin (OECD Science, Technology and Industry Policy Papers, 2019)
This document presents nine innovation policy initiatives from different OECD countries that support research and innovation for sustainable development by embracing systemic solutions to address the challenge. The three types of initiatives reviewed include: i) grant schemes that support the development of environmental technologies; ii) programmes that foster research collaborations to address environmental challenges; and iii) smart city initiatives that support sustainable development in urban areas often by leveraging the use of digital technologies. The nine policy initiatives, which were selected based on an overview of initiatives gathered by the EC-OECD STIP Compass database, are described with regards to their main features, including policy objective, policy instrument(s) implemented, target groups, selection criteria and procedures, implementation challenges faced as well as their impact